(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
This paper investigates speech compression as a crucial tactic in translation, particularly focusing on the challenges of simultaneous interpretation. Recent research has emphasized the need to alleviate the heavy workload of translators. Professional simultaneous interpreters aim to convey the main message while navigating linguistic and cultural disparities between languages, making compression essential.